Auditor Switches by Failing Firms. - Schwartz, Kenneth B.; Menon, Krishnagopal (The Accounting Review, 1985)
ABSTRACT: This study examines the motivations for failing firms to change auditors. Some of the factors that could influence auditor switching include audit qualifications, reporting disputes, management changes, audit fees, and insurance needs. Annual reports, 10-Ks, and proxy statements were used to gather data for a sample of 132 failing (bankrupt) firms and a matched-pair sample of nonfailing firms. The investigation's findings strongly supported our prior expectations that failing firms have a greater tendency to switch auditors than do healthier firms. Other findings revealed that neither audit qualifications nor management changes were statistically associated with auditor displacement in failing firms. Failing firms that changed auditors did display a preference to move to a different class of CPA firms. Also, size did not appear to matter with respect to the observed auditor switching among the failing firms, although it appeared to have some effect among control firms. Overall, our study's major findings suggest a definite need to control for the presence of financial distress in studies on auditor switching.